Agroindustrial Sector of the Tambov Region in the System of Providing the Russian Population with Food - V. Nikitin, A.; Yu. Antsiferova, O. (International Journal of Engineering and Technology, 2018)
The information and analytical materials evaluate the state and efficiency of the agroindustrial complex functioning in the country and in theÂ Tambov Region, its impact on ensuring food and the populationâ€™s living standard. The main criterial indicators of the export potential were analyzed in terms of qualitative and quantitative indicators for the country and the region. The ways to improve the export potential, as well as to solve the problem of food self-production and to achieve food independence have been offered. TheÂ ways to improve the Russian agricultural producersâ€™ competitiveness, to form efficiently functioning agricultural, raw materials and food markets, to increase the profitability of agricultural producers, to create a favorable investment climate, as well as to increase the volume of investments in theÂ agricultural sector of the economy to grow its production have been developed.Â Â